2015
DOI: 10.1152/ajpregu.00095.2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of leg blood flow restriction during walking on central arterial hemodynamics

Abstract: Walking exercise with limb blood flow restriction (BFR) has been shown to increase muscular mass and strength even if it is performed at low exercise intensities. Despite mounting evidence for its efficacy and the increasing popularity, the safety of BFR exercise in relation to cardiac loads has not been established. The aim of this study was to determine the response of central hemodynamics during the BFR exercise to assess its impact on cardiac load. Fifteen apparently healthy sedentary or recreationally act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 35 publications
(48 reference statements)
3
44
2
Order By: Relevance
“…The similar hemodynamic responses between LI and LI+BFR are in contrast to previous reports that observed increased blood pressures with aerobic BFR exercise to levels greater than an equal-intensity control exercise bout, combined with a greater HR and reduced SV while maintaining _ Q (Renzi et al 2010;Staunton et al 2015;Sugawara et al 2015;Ozaki et al 2010). Typically, such different responses to BFR exercise between studies may be attributed to factors associated with the application of BFR such as cuff width and cuff pressure (Loenneke et al 2012a), and the exercise type (Staunton et al 2015), combined with individual factors such as limb circumference (Loenneke et al 2012a).…”
Section: Treadmillsupporting
confidence: 62%
See 2 more Smart Citations
“…The similar hemodynamic responses between LI and LI+BFR are in contrast to previous reports that observed increased blood pressures with aerobic BFR exercise to levels greater than an equal-intensity control exercise bout, combined with a greater HR and reduced SV while maintaining _ Q (Renzi et al 2010;Staunton et al 2015;Sugawara et al 2015;Ozaki et al 2010). Typically, such different responses to BFR exercise between studies may be attributed to factors associated with the application of BFR such as cuff width and cuff pressure (Loenneke et al 2012a), and the exercise type (Staunton et al 2015), combined with individual factors such as limb circumference (Loenneke et al 2012a).…”
Section: Treadmillsupporting
confidence: 62%
“…LI and LI+BFR required participants to walk at a velocity of 4 km·h −1 as used previously (Sugawara et al. ; Renzi et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An application of BFR during walking exercises has been associated with greater RPE [2,7,30]. In the present study using yoga, there was no significant difference between the conditions in reported RPE throughout the exercise duration.…”
Section: Discussioncontrasting
confidence: 52%
“…While aerobic BFRE is less studied than resistance BFRE, several investigations have compared the haemodynamic responses to an acute bout of aerobic BFRE. Greater elevations in arterial pressures in response to treadmill walking with blood flow restriction applied to the upper thighs compared to non‐restricted exercise at the same intensity have been reported (Renzi, Tanaka, & Sugawara, ; Sugawara, Tomoto, & Tanaka, ). However, the intensities of BFRE and control exercise were not matched based on heart rate or V̇O2 max in these studies.…”
Section: Novel Adaptations Of Remote Ischaemic Preconditioningmentioning
confidence: 87%